KREDIT-MODUL SHAROITIDA TALABALAR TA’LIMINI INDIVIDUALLASHTIRISH MAZMUNI - Arzikulova, S.F. (SCIENCE and SOCIETY, 2025)
The article provides information on the content of individualization of individual training of students in the credit-modular system. The credit-modular system is a system that is aimed at increasing the individual focus of students in this system, organizing training in accordance with the individual educational capabilities of the student, and also discusses the stages of individualization of the limb. This article can be used as theoretical information by representatives of the relevant field.
Keywords: education; individualization; credit module; independent learning; principles; form; methods